2021
DOI: 10.1007/jhep07(2021)191
|View full text |Cite
|
Sign up to set email alerts
|

Sequential deconfinement in 3d $$ \mathcal{N} $$ = 2 gauge theories

Abstract: We consider 3d$$ \mathcal{N} $$ N = 2 gauge theories with fundamental matter plus a single field in a rank-2 representation. Using iteratively a process of “deconfinement” of the rank-2 field, we produce a sequence of Seiberg-dual quiver theories. We detail this process in two examples with zero superpotential: Usp(2N) gauge theory with an antisymmetric field and U(N) gauge theory with an adjoint field. The fully deconfined dual quiver has N nodes, and can be interpreted as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 48 publications
7
53
0
Order By: Relevance
“…In this appendix we revisit the problem of mapping monopole operators when applying Aharony duality [59] locally on a node of a quiver gauge theory. This issue was first investigated in [89,90] in the case of unitary gauge groups and later in [91,92] in the case of SU , U Sp and SO groups (see also appendix A of [93]). Nevertheless, in all of these papers the case in which the dualized gauge node is confined wasn't considered, and this is exactly the case we are interested in.…”
Section: Jhep09(2021)149 C Confining Aharony Duality For Su(2) Quiversmentioning
confidence: 99%
See 1 more Smart Citation
“…In this appendix we revisit the problem of mapping monopole operators when applying Aharony duality [59] locally on a node of a quiver gauge theory. This issue was first investigated in [89,90] in the case of unitary gauge groups and later in [91,92] in the case of SU , U Sp and SO groups (see also appendix A of [93]). Nevertheless, in all of these papers the case in which the dualized gauge node is confined wasn't considered, and this is exactly the case we are interested in.…”
Section: Jhep09(2021)149 C Confining Aharony Duality For Su(2) Quiversmentioning
confidence: 99%
“…The technique of deriving dualities between quiver gauge theories by applying more fundamental dualities locally on a node has recently been exploited a lot, see[65,89,90,[92][93][94][95][96] for some examples in three dimensions where one can apply either Aharony duality[59] or variants with monopole superpotentials[97].…”
mentioning
confidence: 99%
“…We will present an application of the results in this note in two companion papers [33,34]. In [33] we study the duals of a theory with a single gauge group and matter in the a rank-2 representation, U(N ) with a single adjoint field and flavors, or Sp(N ) with a single antisymmetric field and flavors. We produce a dual which is a quiver with N gauge nodes, obtained by sequentially deconfining the rank-2 field.…”
Section: Jhep10(2021)191mentioning
confidence: 99%
“…Ref. [33] studies the cases of an adjoint of U(N ) and the rank-2 anti-symmetric of Sp(N ) (aspects of the latter theory have been discussed in [49,52]). Ref.…”
Section: Jhep10(2021)191mentioning
confidence: 99%
“…A recent results that corroborates this expectation appeared recently in [19,20], where it is shown that 4d mirror symmetry dualities [21,22] (and hence 3d mirror symmetry dualities [23,24]) can be proven using only Intriligator-Pouliot (IP) duality, relating theories with U sp gauge group and fundamental matter. Moreover, in [12] we will use the sequential deconfinement techniques of [25,26] to find a quiver dual of U sp(2N ) with F flavors, and use this deconfined version to prove a knwon self-duality of U sp(2N ) with 4 flavors [27]. This paper is organized as follows.…”
mentioning
confidence: 99%